Predicting the job performance and job satisfaction of male teachers based on the psychological climate prevailing in the education organization - Ahmadianipay, Abbas; Eltiaminia, Siddiqa; Eltiaminia, Nazgol; Eltiaminia, Nematolah (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: Education is the most important social institution emerging from the context of the society and at the same time its creator and developer, and its effect on the progress of the society is quite noticeable. One of the things that can cause lack of performance and job satisfaction is the psychological atmosphere that dominates the organization. Therefore, this research aimed to predict the job performance and job satisfaction of male teachers based on the psychological climate prevailing in the education organization. Method: The research design was descriptive and correlational. The statistical population of the research was made up of all male teachers in two districts of Tehran. Among the statistical population, 162 people were selected and studied as available sampling. In order to collect data, the psychological atmosphere, job satisfaction, and job performance measures were used. After collecting and extracting the data, the participants’ scores were analysed with Pearson’s correlation and linear regression model through SPSS-22. Results: The results showed a significant relationship between the psychological atmosphere governing the organization and job satisfaction and teachers’ job performance. Also, the results showed that the psychological atmosphere governing the organization can predict the teachers’ job satisfaction and job performance. Conclusion: According to the results of the present research, using teachers’ opinions and suggestions and sharing the problems and problems of the organization with them in order to find a solution and correct and improve the work can be an important step in increasing the job performance and consequently the job satisfaction of the teachers.